2018
DOI: 10.1002/jum.14887
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Right and Left Atrial Functions at Midterm After Surgical and Device Atrial Septal Defect Closure: A 2‐Dimensional Speckle‐Tracking Echocardiographic Study

Abstract: Objectives The available literature lacks data on the comparison of the functions of the right atrium (RA) and left atrium (LA) between surgical atrial septal defect (ASD) closure and percutaneous device ASD closure at follow‐up durations of longer than 1 year. We sought to evaluate the RA and LA functions in patients who underwent surgical or device ASD closure between 1 and 5 years postprocedurally. Methods The study population included 30 patients who underwent device ASD closure and 30 who underwent surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
1
9
1
Order By: Relevance
“…In this long-term follow-up, the LA reservoir function, conduit and contraction function of the ASD-D were impaired compared to the control group, but there was no difference in these functions between the ASD-D and ASD-S groups. Our results are very similar to those of Hajizeinali et al, 24) who analyzed data from 1 to 5 years after treatment. They reported reduced reservoir function in the device group, and reduced conduit function in both the device and surgery groups, compared to controls.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this long-term follow-up, the LA reservoir function, conduit and contraction function of the ASD-D were impaired compared to the control group, but there was no difference in these functions between the ASD-D and ASD-S groups. Our results are very similar to those of Hajizeinali et al, 24) who analyzed data from 1 to 5 years after treatment. They reported reduced reservoir function in the device group, and reduced conduit function in both the device and surgery groups, compared to controls.…”
Section: Discussionsupporting
confidence: 92%
“… 28) When analyzing 2D strain of LA, they suggest averaging the measurements of the anterior, inferior, lateral, and septal walls, but several previous studies have excluded the septum from the analysis because of its displacement due to the device or patch. 21) 24) We analyzed global strain without excluding the LA septum, because 2D STE has the ability to distinguish normal deformation from passive device motion without being affected by the global motion of the heart or tethering of the adjacent segments. 29) 30) …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we calculated only LS of the FW as the average strain in three segments of the FW and did not include LS of IAS or global longitudinal strain. 25) We calculated the average of the peak LS of FW during the systolic phase (LSs-FW) in three segments, which indicated LA reservoir function. LS of FW during the early diastolic phase (LSe-FW) indicated LA conduit function.…”
Section: Figurementioning
confidence: 99%
“…[9][10][11][12] Chronic geometrical changes and volume overload in hearts with ASD lead to remodeling of the sarcomeres. 6 Sarcomeres are contractile units of the heart and their changes are the mainstay of the alterations seen in strain values. It is difficult to predict the timing of the initiation of these changes; they might be present at birth or progress as an acquired disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Hajizeinali et al compared LA and RA functions in post-surgical and device closure patients and found reductions in reservoir phase of LA function in the device group, whereas there were reductions in RA strains in post-surgical patients, probably due to surgical incisions. 6 Cakal et al evaluated left-sided strain and strain rates in adult patients with secundum ASD and found no significant difference between patients with ASD and normal subjects. The LV and LA strains increased after device closure.…”
Section: Discussionmentioning
confidence: 99%